A paddling based locomotive mechanism for capsule endoscopes - Park, Sukho; Park, Hyunjun; Park, Sungjin; Kim, Byungkyu (KOREAN SOC MECHANICAL ENGINEERS, 2006)
Diagnosis and treatment using the conventional flexible endoscope in gastro-intestinal tract are very common since advanced and instrumented endoscopes allow diagnosis and treatment by introducing the human body through natural orifices. However, the operation of endoscope is very labor intensive work and gives patients some pains. As an alternative, therefore, the capsule endoscope is developed for the diagnosis of digestive organs. Although the capsule endoscope has conveniences for diagnosis, it is passively moved by the peristaltic waves of gastro-intestinal tract and thus has some limitations for doctor to get the image of the organ and to diagnose more thoroughly. As a solution of these problems, various locomotive mechanisms for capsule endoscopes are introduced. In our proposed mechanism, the capsule-type micro-robot has synchronized multiple legs that are actuated by a linear actuator and two mobile cylinders inside of the capsule. For the feasibility test of the proposed microrobot, a series of in-vitro experiments using small intestine without incision were carried out. From the experimental results, our proposed microrobot can advance along the 3D curved and sloped path with the velocity of about 3.29 similar to 6.26 mm/sec and 35.1 similar to 66.7% of theoretical velocity. Finally, the proposed locomotive mechanism can be not only applicable to micro capsule endoscopes but also effective to advance inside of gastro-intestinal tract.